KAWAL PEMULIHAN EKONOMI USAI PANDEMI - I Ketut Kasna (Jurnal Ilmiah Cakrawarti, 2021)
The handling of the pandemic must not rule out the main factor, namely the health of the citizens themselves. For this reason, the government is expected to be able to ensure the creation of strengthening the domestic industry, especially the medical device industry in anticipation of the outbreak of a pandemic in the future. The Covid-19 pandemic has caused a decline in the economy and activity in various sectors and regions in Indonesia. In the midst of the uncertainty of the situation and the new order of life, business actors, both from the real sector, manufacturing, to the informal sector, need more attention from the government. In addition to the fiscal and monetary policies that have been issued by the government through the economic recovery program, business actors are also required to be able to adapt to the market revolution due to the pandemic.